T14diLys/DOPE Liposomes: An Innovative Option for siRNA-Based Gene Knockdown? - Sophie Meinhard; Frank Erdmann; Henrike Lucas; Maria Krabbes; Stephanie Krüger; Christian Wölk; Karsten Mäder (Pharmaceutics)
Background/Objectives: Bringing small interfering RNA (siRNA) into the cell cytosol to achieve specific gene silencing is an attractive but also very challenging option for improved therapies. The first step for successful siRNA delivery is the complexation with a permanent cationic or ionizable compound. This protects the negatively charged siRNA and enables transfection through the cell membrane. The current study explores the performance of the innovative, ionizable lipid 2-Tetradecylhexadecanoic acid-(2-bis{[2-(2,6-diamino-1-oxohexyl)amino]ethyl}aminoethyl)-amide (T14diLys), in combination with 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), for siRNA delivery and the impact of the production method (sonication vs. extrusion) on the particle properties. Methods: Liposomes were produced either with sonication or extrusion and characterized. The extruded liposomes were combined with siRNA at different N/P ratios and investigated in terms of size zeta potential, encapsulation efficiency, lipoplex stability against RNase A, and knockdown efficiency using enhanced green fluorescent protein (eGFP)-marked colon adenocarcinoma cells. Results: The liposomes prepared by extrusion were smaller and had a narrower size distribution than the sonicated ones. The combination of siRNA and liposomes at a nitrogen-to-phosphate (N/P) ratio of 5 had optimal particle properties, high encapsulation efficiency, and lipoplex stability. Gene knockdown tests confirmed this assumption. Conclusions: Liposomes produced with extrusion were more reproducible and provided enhanced particle properties. The physicochemical characterization and in vitro experiments showed that an N/P ratio of 5 was the most promising ratio for siRNA delivery.